Assessment Framework of the Developmental Level of Number Sense of First‐Grade Primary School Students - Pan, Yuchen; Xu, Wenbin; Chen, Yunxian; Huang, Nana; Wang, Yang (Psychology in the schools, 2025)
ABSTRACT At the beginning of the 21st century, “number sense” was listed as one of the core words in the mathematics curriculum of compulsory education in China, and it has now become one of the core competencies of primary school mathematics. It is necessary to determine the development of number sense of first‐grade primary school students (6–7 years old), which can provide suggestions for teaching. This paper analyzes the connotation of number sense and determines the constituent elements of first‐grade students' number sense, as well as refers to relevant studies in the world, constructing an assessment framework that includes 3 first‐level dimensions and 9 s‐level dimensions: number and quantity (subitizing, counting, cardinality), quantitative relationship (comparing, number order and ordinal numbers, estimating), number operations (decomposition and composition, addition and subtraction, informal multiplication and division), dividing each dimension into multiple development levels from low to high. The test paper consists of nine tasks, and the reliability and validity indexes are moderate, indicating it can be used as an evaluation tool for the development of number sense of first‐grade primary school students. Summary This study aims to construct an assessment framework of number sense and develop tasks, to evaluate the number sense skills of first‐grade primary school students or children who just graduated from kindergarten. The validity of the assessment framework and test was preliminarily validated in the Chinese context. Early childhood mathematics researchers and primary school teachers can benefit from this study, using the framework to understand the number sense skills of a range of students, which can provide insights into how to conduct the initial teaching in primary school.